2013
DOI: 10.1177/0883073813490074
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications Following Pediatric Renal Transplantation

Abstract: We reviewed neurologic complications after renal transplantation in children over a 20-year period. Neurologic complications were classified as early (within 3 months) and delayed (beyond 3 months). Of 115 children, 10 (8.7%) had complications. Early complications were found in 4.35% of patients: seizures in 4 (posterior reversible leukoencephalopathy syndrome due to immunosuppressant toxicity, sepsis/presumed meningitis, and indeterminate) and headaches in 1. One patient with seizures received levetiracetam f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…This is the first observational study on PRES in pediatric heart transplant recipients as prior descriptions are limited to single case reports . PRES occurred in 5.5% of pediatric heart transplant recipients in our study, which is comparable to the reported prevalence after pediatric kidney transplant (4.4%) , but lower than described after pediatric liver transplantation (10%) .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is the first observational study on PRES in pediatric heart transplant recipients as prior descriptions are limited to single case reports . PRES occurred in 5.5% of pediatric heart transplant recipients in our study, which is comparable to the reported prevalence after pediatric kidney transplant (4.4%) , but lower than described after pediatric liver transplantation (10%) .…”
Section: Discussionsupporting
confidence: 76%
“…Multiple case reports and one single‐center study also describe early occurrence of PRES after pediatric liver transplant, within 1–3 weeks of receiving a transplant . In contrast, PRES after pediatric kidney transplant appears to occur both early and late (>3 months after transplant) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular theory relies upon blood–brain barrier dysfunction secondary to hypertension, but blood pressure is normal or mildly elevated in 30% of cases . A second theory is based on the role of endothelial dysfunction due to circulating toxins in sepsis, immunosuppression, and autoimmune disease . Another theory is ischemic edema secondary to focal vasospasm and blood flow reduction, and according to this interpretation, it is speculated that systemic hypertension is finalized at maintaining the cerebral blood flow .…”
Section: Discussionmentioning
confidence: 99%
“…Solid organ transplants performed in the United States in 2015 exceeded 30,000 and continued to increase ( 1 ). Although remarkable advances in transplantation medicine improved the outcomes of allogeneic graft recipients, neurologic complications are still common with variety incidence ranging from 7% to 77% of allograft recipients after HSCT and solid or gan transplantation ( 2 3 4 5 6 7 8 9 10 11 12 ). One of the most deleterious neurologic complications is transplant-associated encephalopathy, which has various etiologies, including the underlying disorder motivating the transplant, immunosuppressant neurotoxicity, metabolic derangement, central nervous system (CNS) infection, and stroke ( 9 12 13 14 15 ).…”
Section: Introductionmentioning
confidence: 99%